Analisis Framing Murray Edelman Dalam Berita “Dampak PT. Medco Terhadap Masyarakat Lingkar Tambang” Pada Media AJNN.net - Adelia Shinta Dwita; Gunawan Wisnu Pramudya; Ade Irma Sukmawati (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
The issue that attracts the public's attention is news about complaints from communities around the mining area which so far have not found a solution in the online media AJNN.net, so this research is conducted to explain the views of a media in that case. This problem arose when the community around the mine felt the impact caused by PT Medco due to air pollution. The impact is felt mainly on the health problems experienced by the community, but PT Medco is ignoring the impact they have caused. Therefore, this research is conducted to see the bias of the AJNN.net media in presenting news. The aim of this research is to identify framing analysis in the online media AJNN.net when presenting news about problems between PT Medco and communities around the mine. The analysis carried out was by using Murray Edelman's framing model and using qualitative methods, a constructivist paradigm, and a narrative approach; so that the results show that the AJNN.net media is in the side of the community around the mining area.